2023
DOI: 10.3390/w15050900
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Nutrients and Carbon Interactions in an Urban Coastal Water during Algal Bloom Period in Zhanjiang Bay, China

Abstract: Nutrients and carbon play important roles in algal bloom and development. However, nutrients and carbon interactions in the period of the spring algal bloom are not well understood. The aim of this study is to explore the nutrients and carbon interactions in the period of the spring algal bloom covering an urban Jinsha Bay (JSB) coastal water in Zhanjiang Bay (South China Sea) using in situ multidiscipline observation. The results showed that the average concentration of total nitrogen (TN), total phosphorus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The rainy seasons are periods of frequent agricultural activities. As Zhanjiang is a city dominated by industry and agriculture, the extensive use of chemical fertilizers in agricultural production and the discharge of industrial and domestic wastewater has brought a large amount of nutrients to Zhanjiang Bay (Li et al, 2020;Zhang et al, 2020;Zhou et al, 2021;Zhang et al, 2023). During rainy seasons, nitrogen fertilizer is the dominant nutrient input in the bay (accounting for 36%), following by soil nitrogen (32%) and sewage and manure (31%) (Li et al, 2020).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The rainy seasons are periods of frequent agricultural activities. As Zhanjiang is a city dominated by industry and agriculture, the extensive use of chemical fertilizers in agricultural production and the discharge of industrial and domestic wastewater has brought a large amount of nutrients to Zhanjiang Bay (Li et al, 2020;Zhang et al, 2020;Zhou et al, 2021;Zhang et al, 2023). During rainy seasons, nitrogen fertilizer is the dominant nutrient input in the bay (accounting for 36%), following by soil nitrogen (32%) and sewage and manure (31%) (Li et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…However, this also increases the intrusion of high-salinity seawater with relatively oligo nutrients (Lao et al, 2022), which can dilute the pollutant loads in the bay. In addition, Zhanjiang Bay is located in the tropical region, with sufficient light in winter and spring and relatively high temperature (Figure 2A), which is conducive to the growth of algae, particularly for the macroalgae (Zhang et al, 2022;Zhang et al, 2023), and thus the Chl-a is still at a relatively high level during this period (Figure 2). In the case of a reduced external nutrient supply, algae growth will consume a certain amount of nutrients (Zhang et al, 2022;Zhang et al, 2023).…”
Section: Figurementioning
confidence: 99%
“…The results show that COD, DIN (p < 0.05), and DIP (p < 0.05) showed a significant positive correlation. In addition, it can be concluded that in the relationship discussed in this paper, COD, DIN, and DIP all increase with the increase of nitrogen content in the environment and decrease with the increase of salinity content [78,79]. All kinds of environmental factors are related to nutrients because water affects the reproduction rate of primary producers by changing the water temperature, salinity, and pH, and the number of primary producers determines the amount of nutrients.…”
Section: Key Environmental Factors Affecting Nutrients In Tieshan Baymentioning
confidence: 65%
“…In 2010, the DIP levels were significantly higher in the inner bay than in the upper bay because of the transport of large amounts of phosphate from various factories and sewage discharge points (Zhang et al, 2021). In addition, DIN levels in ZJB are mainly caused by the discharge of urban agricultural fertilizers and industrial and domestic wastewater (Li et al, 2020;He et al, 2023;Zhang et al, 2023a), which is consistent with other offshore waters such as the Black Sea (Alkan et al, 2022), the Chinese coast (Wang et al, 2020) and the Elbe estuary in Germany (Dähnke et al, 2008). Freshwater runoff is the primary source of terrestrial DIN in the upper bay, with N fertilizer and soil N contributing approximately 70%, and sewage and feces contributing the remaining 30% (Li et al, 2020).…”
Section: Terrigenous Input Contributes To Eutrophicationmentioning
confidence: 99%
“…An excess or deficiency of either element can result in N or P depletion, thereby impeding the development of phytoplankton and influencing primary productivity. Moreover, excessive nutrient levels may cause significant phytoplankton blooms and high primary productivity, resulting in eutrophication, red tides, algal blooms, water hypoxia, and acidification (Wang et al, 2021a;Zhang et al, 2023aZhang et al, , 2023b. These factors can degrade the affected environments, directly threaten biodiversity and habitats, and cause massive mortality of marine organisms, ultimately harming marine ecosystems and human society (Deegan et al, 2012;Mauŕe et al, 2021;He et al, 2023).…”
Section: Introductionmentioning
confidence: 99%